FACTORS THAT INFLUENCE WORLD CLASS MANUFACTURING ADOPTION IN DEVELOPING COUNTRIES - Maisiri, Whisper; Makwangudze, Franco; Bilibana, Lisolethu (The South African Journal of Industrial Engineering, 2023)
The prevailing global competitive environment requires continuous improvement approaches that integrate the entire organisation, from strategic management to operational performance. World class manufacturing (WCM) is a continuous improvement strategy that defines the logic, rigour, and detail of how organisations can achieve sustainable operational performance and customer satisfaction improvements. The paper investigates the factors influencing the successful implementation and sustaining of WCM in the South African manufacturing industry. A qualitative descriptive approach is employed to probe the views and opinions of WCM practitioners in a global manufacturing company with a footprint in South Africa and in other African countries, who were enrolled via purposeful sampling. The findings revealed that management commitment significantly influences achieving a successful WCM system. Furthermore, running WCM as a system could mitigate noticeable barriers identified in this study. The study could substantially enhance industrial engineering practice by revealing aspects to consider when implementing and running a WCM system.